Expression of nonmuscle myosin IIC is regulated by non-canonical binding activity of miRNAs - Banerjee, Kumarjeet; Saha, Shekhar; Das, Shaoli; Ghosal, Suman; Ghosh, Indranil; Basu, Abhimanyu; Jana, Siddhartha S. (iScience, 2023)
The expression of mechanoresponsive nonmuscle myosin II (NMII)C is found to be inducible during tumor progression, but its mechanism is yet to be explored. Here, we report a group of microRNAs (mmu-miR-200a-5p, mmu-miR-532-3p, mmu-miR-680, and mmu-miR-1901) can significantly repress the expression of nonmuscle myosin IIC (NMIIC). Interestingly, these microRNAs have both canonical and non-canonical binding sites at 3/UTR and coding sequence (CDS) of NMIIC’s heavy chain (HC) mRNA. Each of the miRNA downregulates NMHC-IIC to a different degree as assessed by dual-luciferase and immunoblot analyses. When we abolish the complementary base pairing at canonical binding site, mmu-miR-532-3p can still bind at non-canonical binding site and form Argonaute2 (AGO2)-miRNA complex to downregulate the expression of NMIIC. Modulating the expression of NMIIC by miR-532-3p in mouse mammary tumor cells, 4T1, increases its tumorigenic potential both in vitro and in vivo. Together, these studies provide the functional role of miRNA’s non-canonical binding mediated NMIIC regulation in tumor cells. [Display omitted] •Expression of nonmuscle myosin IIC (NMIIC) can be regulated by miRNAs•Non canonical bindings of miRNAs add the efficacy of canonical bindings•Heterofilament formation of NMIIC with NMIIA and -IIB regulate cortical tension in cell Biochemistry; Molecular mechanism of gene regulation; Cell biology